HOW TO MAP THE MEANING OF “SEE” IN KUPANG MALAY - David Samuel Latuperissa (Lingual: Journal of Language and Culture, 2016)
Lexicon ‘See’ as an English verb that means ‘perceive with the eyes’has different form oflexicon and different semantics meaning in Kupang Malay Language (KML). The lexiconsthat refer to ‘see’ are ‘lia’,‘loti’,‘malerok’, ‘maloi’ and‘pe’emata’. Those five lexicons havetheir own meaning. In order to understand those words deeply, such matters were analysedby a study using Natural Semantic Metalanguage (NSM) theory.By applying descriptivequalitative method and paraphrase/ explication technique, the slightly different semanticfeatures of ‘lia’,‘loti’,‘malerok’, ‘maloi’ and‘pe’emata’ can be comprehensively revealed.